Enhanced Performance of Cuk and Boost–Based High-Gain Step-Up DC/DC Converter - Preeti Sharma; Sara Hasanpour; Rajneesh Kumar (International Transactions on Electrical Energy Systems)
This article presents a high-gain step-up DC/DC converter based on the Cuk topology for renewable energy applications. The converter employs an auxiliary circuit to achieve less input current ripple, significantly reducing the input inductor size compared to conventional converters. Therefore, the inductor’s equivalent series resistance (ESR) will be substantially lowered to improve power efficiency. Introducing passive clamp capacitors further enhances efficiency by alleviating voltage stress on the main power switch. Comparative studies with other similar converters highlight the unique benefits of converter design. This converter uses a coupled inductor (CI) and a voltage multiplier circuit to achieve high voltage gains. The following article introduces the principle of operation for a proposed topology and analyzes voltage gain, voltage stress, and efficiency. A comprehensive comparison with the most recent counterparts is also included. Finally, a theoretical analysis is verified using a 200-W (30 V/310 V) sample prototype.